Questions of Immortality in a Fragment by Sappho: Прашања за бесмртноста во фрагмент од Сафо - Miglena, Nikolchina; Kirkova, Anastazija (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Miglena Nikolchina | Миглена Николчина Title (English): Questions of Immortality in a Fragment by Sappho Title (Macedonian): Прашања за бесмртноста во фрагмент од Сафо Translated by (English to Macedonian): Anastazija Kirkova | Анастазија Киркова Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 155-168 Page Count: 13 Citation (English): Miglena Nikolchina, “Questions of Immortality in a Fragment by Sappho,” Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 155-168. Citation (Macedonian): Миглена Николчина, „Прашања за бесмртноста во фрагмент од Сафо“, превод од англиски Анастазија Киркова, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 155-168.